Media archaeology : approaches, applications, and implications - Huhtamo, Erkki; Parikka, Jussi, 1976- (University of California Press, 2011)
This book introduces an archaeological approach to the study of media - one that sifts through the evidence to learn how media were written about, used, designed, preserved, and sometimes discarded. Edited by Erkki Huhtamo and Jussi Parikka, with contributions from internationally prominent scholars from Europe, North America, and Japan, the essays help us understand how the media that predate today's interactive, digital forms were in their time contested, adopted and embedded in the everyday. Providing a broad overview of the many historical and theoretical facets of Media Archaeology as an.